VALUATION FOR PROFIT DETERMINATION. - Graham, Robert F. (The Accounting Review, 1940)
The article discusses various issues related to valuation for profit determination. For many years controversy has centered upon the question: "Should depreciated cost or should some form of present value of fixed assets be reflected in the balance sheets of business organizations?" Many cases involving valuation have been before the courts. Of these, the leading accounting and financial cases pertain to rate-fixing, the recapture clause, taxation, and transactions between corporations and their promoters, inter alia. Few cases relate to the question and then only indirectly. The opinions of the United States Securities and Exchange Commission are more helpful. From the investor's viewpoint the profit-and-loss statement is of primary interest in that it furnishes information necessary to measure the success of management in accomplishing the fundamental purpose of a business venture, making profits, and gives some indication of earning capacity and future prospects. Profit determination over the span of an enterprise's life is a relatively simple matter.